2019
DOI: 10.3389/fneur.2019.00275
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Feasibility of Pipeline Embolization Device Compared With Stent-Assisted Coiling to Treat Non-saccular, Unruptured, Intradural Vertebral Artery Aneurysms

Abstract: Object: The pipeline embolization device (PED) has been used to treat non-saccular, unruptured, intradural vertebral artery aneurysms at some institutions. However, there is an absence of large controlled studies validating the feasibility of this treatment. This study aimed to explore the therapeutic feasibility of PED by comparing PED treatment with controlled stent-assisted coiling (SAC). Materials and Methods: Thirty-two PED procedures were matched in a 1:2 manner with 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…We assessed the full text of 111 studies and excluded 97 based on criteria. Finally, 14 studies 12,[18][19][20][21][24][25][26][27][28][29][30][31][32] were included for meta-analysis. Figure 1 shows a flow diagram of the study selection process.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed the full text of 111 studies and excluded 97 based on criteria. Finally, 14 studies 12,[18][19][20][21][24][25][26][27][28][29][30][31][32] were included for meta-analysis. Figure 1 shows a flow diagram of the study selection process.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…18,31 Eight studies were multicenter and six were single-center case series. Thirteen studies 12,[18][19][20][21][24][25][26][27][28][29]31,32 reported aneurysm occlusion rates and all reported procedurerelated neurological complication rates. Our meta-analysis included a total of 659 patients with 676 posterior circulation aneurysms treated with FDs.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, complete occlusion also occurred in three PAOs without any recanalization and recurrence. Likewise, Zhang et al (21) report 93.3% nearly complete and complete occlusion rate of unruptured vertebral no-saccular aneurysm after PED placement in 32 cases series (21). Kuhn et al (10) reported 100% nearly complete and complete occlusion rate in six patients with unruptured vertebral aneurysms.…”
Section: Discussionmentioning
confidence: 98%
“…9 Several factors such as age, sex, smoking, fusiform-type aneurysms, small aspect ratios, and dome-neck ratios have been reported to be predictors of incomplete or complete occlusion. [10][11][12][13][14][15][16][17] However, there is debate about outcomes when using these factors because of limited analysis of the confounding factors. Moreover, the follow-up imaging rate of incomplete occlusion is sometimes insufficient (around 50% at 6 months).…”
mentioning
confidence: 99%